Is the use of Willdenowia incurvata (Restionaceae) for construction at Melkkraal in the Northern Cape sustainable? - Watson, Julia (Department of Biological Sciences, 2017)
The aim of this study is to evaluate the use of Willdenowia incurvata for the construction of dwellings on a farm outside Nieuwoudtville in the Northern Cape. The research intends to determine how much of the resource (Willdenowia incurvata) is used, the method of utilisation and whether this is environmentally sustainable. An extensive survey of each house in the area was included as a vital part of the study. We did transects to asses the biomass of Willdenowia incurvata in the field; we mapped areas where harvesting takes place; and we performed experimental harvests to determine the typical size and amount of restio used per metre during house construction. On average, it was found that each round house used 2 626kg of restios (wet weight), and rectangular houses used 1 189kg of restios. We found that patch size varied (from 0.19ha to 9.91 ha) and patch biomass varied (from 21 041 hg/ha - 54 021 kg/ha) in the harvested areas. Utilising the general growth rate of Willdenowia incurvata (from Pierce, 1984) and the results of the calculated biomass present in the field and on the houses, three important conclusions were drawn. Firstly, it was found that the amount of restios used as construction material found on the 77 houses in the area is one third less than the amount of restios available in the harvested patches (xkg restios in harvested patches, xkg on houses). Secondly, if harvesting for a few houses (i.e. 10) takes place every five years, it seems that the use of Willdenowia incurvata is sustainable. Therefore no changes to the harvesting method, frequency and intensity are apparently necessary. Thirdly, the harvested areas have a higher density of restios per hectare than the unharvested areas. The use of Willdenowia incurvata for dwelling construction on the farm outside Nieuwoudtville appears to be environmentally sustainable from the findings of this study. It is important to note that this is a snapshot view of the situation, and that assessments of sustainable harvesting practices need to be long term, and continuously reviewed.